2022
DOI: 10.3390/ma15175907
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Studies on Graphene-Aluminium Nano Composites for Aerospace Launch Vehicle External Fuel Tank Structural Application

Abstract: From the aspect of exploring the alternative lightweight composite material for the aerospace launch vehicle external fuel tank structural components, the current research work studies three different grades of Aluminium alloy reinforced with varying graphene weight percentages that are processed through powder metallurgy (P/M) route. The prepared green compacts composite ingots are subjected to microwave processing (Sintering), hot extruded, and solution treated (T6). The developed Nano-graphene reinforced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Experimental nanostructural studies on graphene-Al nanocomposites for aerospace applications have confirmed the Molecular Dynamics (MD) simulations [ 22 ]. The enhancement of the mechanical properties exhibited by the graphene-reinforced metal have been ascribed to the lamellar fine grain structure of the nanofiller.…”
Section: The Engineering Of Graphenementioning
confidence: 89%
See 2 more Smart Citations
“…Experimental nanostructural studies on graphene-Al nanocomposites for aerospace applications have confirmed the Molecular Dynamics (MD) simulations [ 22 ]. The enhancement of the mechanical properties exhibited by the graphene-reinforced metal have been ascribed to the lamellar fine grain structure of the nanofiller.…”
Section: The Engineering Of Graphenementioning
confidence: 89%
“…The effective transfer of the strain to the filler enables the processing of Al/graphene powders via the traditional metallurgical routes. The structural components of the external fuel tanks of launch vehicles are fabricated using a microwave powder-sintering method followed by hot extrusion [ 22 ].…”
Section: The Engineering Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Metal matrix composites are widely used in aerospace and automotive industries for their excellent properties such as high strength-to-weight ratio and low coefficient of thermal expansion. In recent years, fruitful results have been achieved by using nano-phase reinforced metal matrix composites such as carbon nanotubes and graphene [ 12 , 13 ], which have led to the improvement of the composites in terms of hardness, strength and wear resistance [ 14 , 15 , 16 , 17 , 18 ]. Graphene is highly preferred for its excellent mechanical properties such as high Young’s modulus and high strength.…”
Section: Introductionmentioning
confidence: 99%
“…In many respects, graphene is considered to be an alternative to silicon device applications owing to its exceptional band structure (relatively zero bandgap) characteristics, outlining its improved optical properties and electrical competences. Besides, graphene is becoming increasingly used in the manufacture of lightweight and strong body parts for vehicles [3]. However, reproducible and stable techniques to yield larger amount and high-quality crystallite graphene at an industrial scale to compete the already commercialized silicon-based devices hold out to be the most worrisome impediment to producing graphene.…”
Section: Introductionmentioning
confidence: 99%